Dynamical behavior of a fractional-order epidemic model for investigating two fear effect functions - Thirthar, Ashraf Adnan; Abboubakar, Hamadjam; Alaoui, Abdesslem Lamrani; Nisar, Kottakkaran Sooppy (Results in control and optimization, 2024)
Using the Caputo operator, a model for a fractional-order epidemic is developed to investigate the fear effect in a pathogenic environment and vaccination procedure. First, we examine if the proposed model is positive. Next, based on the value of the control reproduction number Rc, we compute both the control reproduction and strength numbers and derive the stability criteria of the disease-free equilibrium. In fact, we use the comparison theorem to show that the disease-free equilibrium point is globally asymptotically stable whenever Rc<1. Next, we prove that the solutions of the fractional model exist and are unique. Finally, several numerical simulations are conducted to verify our theoretical results.